2009
DOI: 10.1167/iovs.08-2493
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of an Antioxidant, Lutein, during Retinal Inflammation

Abstract: The present data revealed that the antioxidant lutein was neuroprotective during EIU, suggesting a potential approach for suppressing retinal neural damage during inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
105
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(111 citation statements)
references
References 42 publications
6
105
0
Order By: Relevance
“…14,15 In this model, innate immunity causes an impairment in visual function, which can be recorded by electroretinogram (ERG), [15][16][17] and abnormal leukocyte adhesion, which is related to abnormal circulation caused by inflammatory cytokines produced in the retina. 18 The ERG of these mice shows impaired photoreceptor cell function that is associated with the excessive STAT3-dependent degradation of rhodopsin, a visual substance.…”
mentioning
confidence: 99%
“…14,15 In this model, innate immunity causes an impairment in visual function, which can be recorded by electroretinogram (ERG), [15][16][17] and abnormal leukocyte adhesion, which is related to abnormal circulation caused by inflammatory cytokines produced in the retina. 18 The ERG of these mice shows impaired photoreceptor cell function that is associated with the excessive STAT3-dependent degradation of rhodopsin, a visual substance.…”
mentioning
confidence: 99%
“…The reduction of free radicals and oxidative stress through the administration of lutein (Dilsiz et al, 2006;Li et al, 2009) During the past decade, numerous studies have investigated neuroprotective strategies to reduce / prevent retinal cell death. Recently, intensive efforts have been made to explicate the neuroprotective effects of carotenoids in ocular diseases in vivo (Li et al, 2009;Muriach et al, 2006;Sasaki et al, 2009) and in vitro (Li and Lo, 2010;Nakajima et al, 2009). Various carotenoids are present in human plasma, but only the xanthophylls lutein and zeaxanthin are found in retina in considerable amounts (Junghans et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…LPS was injected into the mice intraperitoneally (ip) to induce EUI, then lutein was administered by subcutaneous (sc) injection. It is suggested that lutein was a protective supplement on photoreceptor cells by decreasing production of reactive oxygen species which were causing visual damages, reduced rhodopsin (RHO) levels and induced GFAP expressions [83].…”
Section: Role Of Lutein and Zeaxanthin In Uveitismentioning
confidence: 99%
“…Lutein and zeaxanthin, which are also called macular xanthophylls, show their effects by filtering high energy visible light, mostly with a peak of absorption at 446 nm and ultraviolet radiation lesser, inhibiting lipid peroxidation and reducing reactive species such as singlet oxygen and hydroxyl radical [46][47][48]. These carotenoids have several benefits on human health, including neuroprotective effects [49][50][51], anti-carcinogenic effects [52][53][54][55], anti-diabetic effects [56][57][58], cardioprotective effects [59][60][61], protective effects on skin damages and ocular diseases [62][63][64][65]. Particularly, several studies showed the role of lutein and zeaxanthin in eye diseases.…”
Section: Introductionmentioning
confidence: 99%